Reproductive parameters of Hypsiboas punctatus(Schneider 1799) (Anura: Hylidae) in the south limit of its distribution area - Antoniazzi, Carolina E. (2013)
Hypsiboas punctatus(Schneider 1799) has a wide distribution in South America, throughout a latitudinal and environmental gradient (tropical/temperate), thus, supporting significantly different pressures among populations. Until now, only tropical populations’ reproductive parameters have been recorded. Then, our goal was to study reproductive parameters on a population inhabiting a temperate climate region to evaluate differences with those inhabiting tropical regions. Studied frogs were smaller than those from tropical regions. There was no correlation between weight and size of males and their testicles volume. Conversely, females’ weight and size was positively correlated to their fertility. Fat bodies were developed in males but absent in females. When compared with other studies, our results showed the variability in reproductive parameters of H. punctatusbetween tropical and temperate regions. This variability could be the result of phenotypic plasticity and/or genetic differentiation between distant populations. This variability may be one of the keys that allow H. punctatusto thrive in diverse ecosystems with different characteristics and environmental pressures.